Contrasting patterns of viral load response in transplant recipients with BK polyomavirus DNAemia on leflunomide therapy. (3rd April 2013) - Cuellar‐Rodriguez, Jennifer; Stephany, Brian; Poggio, Emilio; Mossad, Sherif B.; Goldfarb, David; Lard, Michelle; Askar, Medhat; Fatica, Richard; Srinivas, Titte; Braun, William; Shoskes, Daniel; Flechner, Stuart; et al.
Abstract Background Reduction in immunosuppression is considered the therapy of proven benefit for BKV infection in renal transplantation, but the use of leflunomide has also been reported. It was observed at this center that the patterns of viral load response while on leflunomide appear to fall into two distinct types. Methods Medical records of 22 kidney and kidney‐pancreas recipients at a single center who received leflunomide therapy for BKV DNAemia were reviewed. Information was collected on demographics, BKV viral loads, other antiviral therapy, immunosuppressive drug levels and doses, adverse effects, and graft and patient outcomes. Results Eighteen of 22 cleared BKV viremia, and 12 of 22 had preserved allograft function; only two graft losses occurred in the screening era among leflunomide‐treated patients. Two patterns of viral load reduction were observed, termed the "smooth" and the "zigzag" pattern, which differed in mean time to clear of BKV DNA (2.9 vs. 19.5 months, p = 0.0073). Graft preservation was correlated with lower serum creatinine (SCr) at the start of leflunomide therapy. Conclusions Long courses and "zigzag" fluctuations in viral load can occur in patients who eventually clear BKV on leflunomide with preserved allograft function. Intermittent increases in viral load do not necessarily portend therapeutic failure. Although the utility of leflunomide is still debated in the transplant community, this information may be useful to clinicians who choose to use it in selected patients.